MENGURUS AGENDA ABAD 21 cabaran dan persiapan dalam era globalisasi - Wan Liz Ozman Wan Omar (Golden Books Centre Sdn Bhd, 2000)
Vision towards the 21st century in Malaysia, with emphasis on Islam, industry, politics, and socio-economy.